Urinary KIM-1 and AQP-1 in patients with clear renal cell carcinoma: Potential noninvasive biomarkers - Mijušković, Mirjana M; Stanojević, Ivan; Milović, Novak; Cerović, Snežana; Petrović, Dejan; Jovanović, Dragan; Aleksić, Predrag; Kovačević, Božidar; Andjelić, Tamara; Terzić, Brankica; Djukić, Mirjana; Vojvodić, Danilo (Vojnosanitetski pregled, 2016)
Background/Aim. Kidney injury molecule-1 (KIM-1) and aquaporin-1 (AQP-1) are potential early urinary biomarkers of clear renal cell carcinoma (cRCC). The aim of this study was to ascertain relationship between the urine concentrations KIM-1 and AQP-1 with tumor size, grade, pT stage and type of operation (radical or partial nephrectomy) in patients with cRCC. Methods. Urinary concentrations of urinary KIM-1 (uKIM-1) and urinary AQP-1 (uAQP-1) were determined by commercially available ELISA kits. The analysis included 40 patients undergoing partial or radical nephrectomy for cRCC and 40 age- and sex-matched healthy adult volunteers. Results. The median preoperative concentrations of KIM-1 in the cRCC group [0.724 ± 1.120 ng/mg urinary creatinine  (Ucr)] were significantly greater compared with controls (healthy volunteers) (0.210 ± 0.082 ng/mgUcr) (p = 0.0227). Postoperatively, uKIM-1 concentration decreased significantly to control values (0.177 ± 0.099 ng/mgUcr vs 0.210 ± 0.082 ng/mgUcr, respectively). The size, grade and stage of tumor were correlated positively with preoperative uKIM-1 concentrations. Contrary to these results, concentrations of uAQP-1 in the cRCC group were significantly lower (0.111 ± 0.092 ng/mgUcr) compared with the control group (0.202 ± 0.078 ng/mgUcr) (p = 0.0014). Postoperatively, the concentrations of uAQP-1 increased progressively up to control values, approximately. We find no significant correlation between preoperative uAQP-1 concentrations and tumor size, grade and stage. Conclusion. uKIM-1 was found to be a reliable diagnostic marker of cRCC, based on its significantly increased values before and decreased values after the nephrectomy.
Keywords: kidney neoplasms; diagnosis; biological markers; urine; nephrectomy